Řízení rizik ve stavebním podniku - Šrámková, Michaela (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Bakalářská práce se zaměřuje na řízení rizik ve stavebním podniku. Práce je rozdělena na teoretickou a praktickou část. Teoretická část řeší rizika v projektech, přináší informaci o základním rozdělení a řízení. Praktická část pracuje již se získanými teoretickými znalostmi na konkrétní stavební zakázce, zahrnuje identifikaci rizik, ohodnocování a nakonec jejich ošetření, aby došlo ke snížení dopadu nebo jeho úplnou eliminaci.

The bachelor thesis focuses on risk management in a construction company. The work is divided into theoretical and practical part. The theoretical part introduces the risks in projects, provides information about the basic division and management. The practical part works with the already acquired theoretical knowledge on a specific construction contract, includes the identification of risks, evaluation and finally their treatment to reduce the impact or eliminate it completely.
Risk Management inside Construction Company
Keywords: Riziko; management rizika; řízení rizik; identifikace rizika; kvantifikace rizika; analýza rizika; SWOT analýza; RIPRAN™; hodnota rizika; scénář rizik; pravděpodobnost rizika; ošetření rizik.; Risk; management risk; risk level; risk identification; risk quantification; risk analysis; SWOT analysis; RIPRAN™; value risk; scenario risk; probability of risk; risk treatment.